2017
DOI: 10.4306/pi.2017.14.4.483
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Mind-Body Training on Cytokines and Their Interactions with Catecholamines

Abstract: ObjectiveMind-body training (MBT) may control reactions to stress and regulate the nervous and immune systems. The present study was designed to assess the effects of MBT on plasma cytokines and their interactions with catecholamines.MethodsThe study group consisted of 80 subjects who practice MBT and a control group of 62 healthy subjects. Plasma catecholamine (norepinephrine, NE; epinephrine, E; and dopamine, DA) and cytokine (TNF-alpha, IL-6, IFN-gamma, and IL-10) levels were measured, and the differences b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 39 publications
1
21
0
Order By: Relevance
“…After watching an online video, participants were instructed to follow the MBT expert and to record their daily practice on the paper provided. The program consisted of movement-based meditation, which was designed to calm one’s mind, let negative emotions out, and to concentrate on bodily sensations 7 – 9 . The protocol of the program is described in detail in Supplementary Note.…”
Section: Methodsmentioning
confidence: 99%
“…After watching an online video, participants were instructed to follow the MBT expert and to record their daily practice on the paper provided. The program consisted of movement-based meditation, which was designed to calm one’s mind, let negative emotions out, and to concentrate on bodily sensations 7 – 9 . The protocol of the program is described in detail in Supplementary Note.…”
Section: Methodsmentioning
confidence: 99%
“…27,[36][37][38] It had also been found that meditation, as well as yoga practices, is capable of significantly increasing vagal tone and therefore could not only be effective against psychologic stress-based issues, including trauma, 39,40 but inflammatorybased diseases as well. 16,[41][42][43][44][45][46] Included in this consideration are studies documenting effects of a diverse range of meditative and yoga practices to promote anti-inflammatory and typically reduce proinflammatory cytokine activity, incuding natural killer (NK) cell activity and NK and T cell cytokine production, [45][46][47][48][49][50] which has been a topic of two systematic reviews. 51,52 For example, Bower et al 49 showed that 6 weeks of 20-min daily mindfulness meditation resulted in a significant downregulation of a 19-transcript composite of proinflammatory genes and a significant reduction of activity of the proinflammatory transcription factor nuclear factor kappa B (NF-kB).…”
Section: Anti-inflammatory Effects Associated With Meditation and Yogmentioning
confidence: 99%
“…Other studies show decreases in the circulating levels of the proinflammatory cytokine interleukin (IL)-12 and increases of the anti-inflammatory cytokine IL-10. 47,48,50 In specific patient groups or obese individuals, other studies document reductions in circulating levels of C-reactive protein (CRP) and IL-6, 49,50,53 although these findings were not replicated by some investigators. 48 Some of the cytokine-related effects of seated meditation, breathing practices, and yoga asana practices are related to a reduction in sympathetic nervous system activation, as evidenced by parallel reductions in levels of the catecholamines epinephrine and norepinephrine.…”
Section: Anti-inflammatory Effects Associated With Meditation and Yogmentioning
confidence: 99%
See 1 more Smart Citation
“…Its effects have been investigated in various settings such as randomized controlled trials for novice or cross-sectional studies for long-term meditators; off/online training; healthy individuals, and breast cancer patients. They include psychological improvements such as decreases in stress, [24] anxiety, [28] depression, [23] fatigue [28] and increases in positive effect, [24] quality of life [28] ; behavioral improvements such as increases in sleep quality, [22,23] problem solving [31] ; physiological effects such as increases in plasma nitric oxide, [21] dopamine, [24] and interleukin 10 [30] ; brain structural changes such as thickening of prefrontal cortex area [27] and alterations in conectivities between insula and several brain regions. [20] Findings in certain psychological improvements indicate its association with epigenetic changes.…”
Section: Introductionmentioning
confidence: 99%